Organic matter characteristics of Eocene source rocks with different lithologies in Baiyun Sag of Pearl River Mouth Basin and their geological significance - Yue CHEN; Xiaojun ZHU; Lili ZHANG; Xuhong XIANG; Xiang ZENG; Weilin ZHU (Shiyou shiyan dizhi)
In the deep-water area of the Zhu Ⅱ Depression of the Pearl River Mouth Basin, the Baiyun Sag develops three types of source rocks: mudstone, carbonaceous mudstone, and coal. Existing studies lack experimental data support, making it difficult to accurately assess the differences in hydrocarbon generation potential among source rocks with different lithologies and from different regions. To clarify the lithologies and hydrocarbon generation potential of Eocene source rocks in the Baiyun Sag, comprehensive methods, including thin-section identification, X-ray diffraction analysis, palynofacies identification, and organic geochemical analysis, were used to systematically conduct lithological division, organic matter composition analysis, and hydrocarbon generation potential evaluation. The Eocene source rocks in the Baiyun Sag showed significant differences in mineral composition and organic matter content, with diverse sedimentary structures. Based on the total organic carbon content and mineral composition characteristics, the source rocks in the Baiyun Sag can be classified into sand-rich mudstone, sand-bearing mudstone, carbonaceous mudstone, and coal. The characteristics of these source rocks with different lithologies vary greatly. The sand-bearing mudstone has a massive structure with a relatively high organic matter abundance, mainly coaly organic matter, and contains some amorphous organic matter. Its source rocks are primarily sapropelic with relatively higher hydrocarbon generation potential and tend to generate oil. Sand-rich mudstone is primarily characterized by a clastic massive structure with a relatively low abundance of organic matter, mainly coaly and sporonic organic matter. The source rocks are mainly humic with relatively smaller hydrocarbon generation potential and tend to generate gas. Carbonaceous mudstone and coal are mainly characterized by discontinuous laminated structures and laminated structures, respectively, with high organic matter abundance, predominantly coaly, woody, and shell-type organic matter. Both are humic source rocks and tend to generate gas. The sand-rich mudstone is mainly distributed in the eastern and southern parts of the sag during the sedimentation periods of the Eocene Enping Formation and Wenchang Formation, the sand-bearing mudstone in the eastern part of the sag during the same periods, and the carbonaceous mudstone and coal in the southern part of the sag during the sedimentation periods of the Lower Wenchang Formation and Enping Formation.